Factors affecting uptake of prostate cancer screening among men at Arua regional referral hospital, Arua city. A cross-sectional study. - Ayikoru, Sharon Immaculate; Nanjego, Victoria; ojale , moses (Student's Journal of Health Research Africa, 2025)
Background Prostate cancer screening is the screening process used to detect undiagnosed prostate cancer in men without signs or symptoms. The study aims to determine the factors affecting the uptake of prostate cancer screening among men at Arua Regional Referral Hospital. Methodology A cross-sectional descriptive purposive study which involved a size of 60 respondents selected using purposive sampling method, data was collected using questionnaires. Data was analyzed manually using tally sheets and results were presented in the form of frequency distribution tables and figures. Results 43 (71.67%) were between the age of 4050 years, and 31 (51.67%) were Madi. The majority 23(38.3%) were Catholics, the Majority 28(46.67%) were civil servants, Majority were married 45(75%), Basing on individual factors, only 16.67% of the respondents had ever been screened for prostate cancer. Most 80% of the respondents had fear of prostate cancer screening with the major reason being fear of stigma with 53.33%. Based on socio-economic factors, the majority 63% of the respondents did not believe in myths about prostate cancer screening, and based on health system-related factors, the majority 46.67% had a distance of 2-4km to the nearest health facility. Conclusion Individual factors were the major factors affecting prostate cancer screening which included less knowledge about prostate cancer screening, and fear of prostate cancer screening however also socio-economic factors like low estimated monthly income and health system-related factors like long distance to the nearest health facility which brought about low uptake of prostate cancer screening among men at Arua Regional Referral Hospital. Recommendation There should be increased awareness through mass media and from health workers about prostate cancer and its screening which should help maintain the present and improve the level of knowledge and practice of prostate cancer screening.